2016
DOI: 10.12973/eurasia.2016.1218a
|View full text |Cite
|
Sign up to set email alerts
|

Successes with Reversing the Negative Student Attitudes Developed in Typical Biology Classes for 8th and 10th Grade Students

Abstract: The purpose of this study is to compare changes in attitudes of students about their study of biology in the classes thought by five biology teachers who experienced an Iowa Chautauqua workshop with and two non-Chautauqua teachers who had no experience with any professional development program. The results indicated that there are significant differences in student attitudes in favor with students of the five biology teachers who experienced of a full year of experiences an Iowa Chautauqua workshop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Tarlowski (2006) found that the effects of direct experiences with nature (examined indirectly by comparing rural vs. urban children) and the biological expertise of parents affected the concepts of humans, mammals and insects held by children. The similar approach was possible to find in the study of Hacieminoglu et al (2016), where authors showed the positive effect of teacher on the attitudes. The condition was, that the teacher had got experiences with any program, which can improve knowledge about some biological topics.…”
Section: Resultsmentioning
confidence: 59%
“…Tarlowski (2006) found that the effects of direct experiences with nature (examined indirectly by comparing rural vs. urban children) and the biological expertise of parents affected the concepts of humans, mammals and insects held by children. The similar approach was possible to find in the study of Hacieminoglu et al (2016), where authors showed the positive effect of teacher on the attitudes. The condition was, that the teacher had got experiences with any program, which can improve knowledge about some biological topics.…”
Section: Resultsmentioning
confidence: 59%